Man, nature, and environmental law - Nathawat, G. S.; Shastri, Satish; Vyas, J. P. (Jaipur : RBSA Publishers, 1988)
In response to one of our most pressing concerns, this series of brief, nontechnical books provides in-depth coverage of selected topics relating to man and his environment. Unified in concept and integrated in approach, the books demonstrate that effective change results from an understanding of the total environment, rather than its independent elements. Treating each subject within the context of the human ecosystem, which includes not only the natural and the man-made but the physical and cultural conditions as well, the authors pay particular attention to the economic use, management, and mismanagement of the environment, and to the prospects for the foreseeable future, derived from the perspective of history and the knowledge of contemporary conditions and trends"--Unedited summary from book cover
Includes bibliographies.
Keywords: Environmental law -- Congresses. -- India